A Correlation Between Asdolescents' Knowledge And Early Marriage Incidents In Thein The Working Area Of Swasti Saba Health Center, Lubuk Linggau City In 2024 - Kharisma M, Gina; Sari, Lezi Yovita; Sulastri, Mepi (Multidisciplinary Journals, 2024)
Early marriage carried out at a young age has a negative impact or risk in a person's life including their health status, both physically and psychologically. Early marriage has an impact on the birth of Low Birth Weight (LBW) children and reproductive health. In 2021 in the Swasti Saba Health Center Work Area, there were around 3,600 children, 8.8% or 388 children who were in early marriage. Knowledge is one of the internal factors in early marriage. The purpose of this research was to determine the relationship between adolescent knowledge about early marriage and the incidence of early marriage in the Swasti Saba Health Center Work Area. This research is an observational analytical study using a Cross Sectional approach. The research respondents were determined by quota sampling technique with a total of 155 adolescent respondents in the Swasti Saba Health Center Working Area aged 15-21 years. The instrument used was a questionnaire. Data analysis used was the Chi-Square test. From the results of the data analysis, the level of knowledge of adolescents about early marriage in the good category was 119 (76.8%) respondents, the incidence of early marriage was 10 (6.5%) respondents. The results of the Chi-Square test obtained a p value = 0.000, so there is a significant relationship between adolescent knowledge and the incidence of early marriage. There is a correlation between adolescent knowledge and the incidence of early marriage. It is expected that students will be able to know the impact of early marriage on life and their health status. And have the knowledge to be able to contribute to preventing early marriage in the future.